The missing linker between SUN5 and PMFBP1 in sperm head-tail coupling apparatus - Ying Zhang (Nature Portfolio, 2021)
The sperm head-to-tail coupling apparatus ensures sperm head-tail integrity, but mechanistic insights remain limited. Here the authors demonstrate that CENTLEIN links and controls the interaction between SUN5 and PMFBP1, indicating that its impairments might be associated with acephalic spermatozoa syndrome.